HIV and symptoms of depression are independently associated with impaired glucocorticoid signaling. (October 2018) - Bekhbat, Mandakh; Mehta, C. Christina; Kelly, Sean D.; Vester, Aimee; Ofotokun, Ighovwerha; Felger, Jennifer; Wingood, Gina; Anastos, Kathryn; Gustafson, Deborah R.; Kassaye, Seble; Milam, Joel; Aouizerat, Bradley; et al.
Highlights: Depressive symptoms associated with elevated baseline expression of Fkbp5 and Nr3c1 . HIV serostatus associated with elevated baseline expression of Fkbp5 and Nr3c1 . Depressive symptoms associated with reduced LPS-induced release of IL-6 and TNF-α. Abstract: Chronic inflammation caused by HIV infection may lead to deficient glucocorticoid (GC) signaling predisposing people living with HIV to depression and other psychiatric disorders linked to GC resistance. We hypothesized that comorbid HIV and depressive symptoms in women would synergistically associate with deficits in GC signaling. This cross-sectional study used samples obtained from the Women's Interagency HIV Study (WIHS). The Centers for Epidemiological Studies (CES-D) was used to define depression in four groups of women from the Women's Interagency HIV Study (WIHS): 1) HIV-negative, non-depressed (n = 37); 2) HIV-negative, depressed (n = 34); 3) HIV-positive, non-depressed (n = 38); and 4) HIV-positive, depressed (n = 38). To assess changes in GC signaling from peripheral blood mononuclear cells (PBMCs), we examined baseline and dexamethasone (Dex)-stimulated changes in the expression of the GC receptor (GR, gene: Nr3c1) and its negative regulator Fkbp5 via quantitative RT-PCR. GR sensitivity was evaluated in vitro by assessing the Dex inhibition of lipopolysaccharide (LPS)-stimulated IL-6 and TNF-α levels. Depressive symptoms and HIV serostatus were independently associated with elevated baseline expression of Fkbp5 and Nr3c1 . Depressive symptoms, but not HIV status, was independently associated with reduced LPS-induced release of IL-6. Counter to predictions, there was no interactive association of depressive symptoms and HIV on any outcome. Comorbid depressive symptoms with HIV infection were associated with a gene expression and cytokine profile similar to that of healthy control women, a finding that may indicate further disruptions in disease adaptation.